Nutritional Status of Tetralogy of Fallot Patients at Dr. Hasan Sadikin General Hospital Bandung - Cafrina, Gabriella; Firman, Armijn; Nugraha, Gaga Irawan (Althea Medical Journal, 2016)
Background: Undernutrition is common in children with congenital heart disease (CHD), especially in developing countries including Indonesia. The objective of the study was to describe the nutritional status of children patients with Tetralogy of Fallot.Methods: This was a cross-sectional descriptive study using 41 medical records of children aged 0â14 years old with Tetralogy of Fallot that visited pediatric outpatient department of Dr. Hasan Sadikin General Hospital in period of January to December 2013. The variable was anthropometric measurement, namely weight-for-age, height-for-age, weight-for-height, and body mass index-for-age. These anthropometric data were analyzed using statistics software, WHO Anthro, and WHO AnthroPlus and were classified based on nutritional status according to WHO. The collected data were displayed in percentage.Results: There were more boys (60.98%) who had Tetralogy of Fallot compared to girls (39.02%). The percentage of undernutrition was 39.02% with 43.75% in 5â14 year old children. The percentage of stunting was 70.73% with 72% in 0â5 year old children. Meanwhile, the percentage of underweight was 52% in children aged 0â5 years old.Conclusions: The percentage of undernourished children with Tetralogy of Fallot is quiet high. Undernutrition occurs more often in 5â14 year old children, while stunting occurs more often in 0â5 year old children. [AMJ.2016;3(2):298â303]DOI:Â 10.15850/amj.v3n2.784